Play It Again: Rock Music Reissues and the Production of the Past for the Present. (14th March 2016) - Bottomley, Andrew J.
Abstract : The reissue is a significant yet under-studied aspect of the music industries and popular music culture. The continual resurrection of recordings via reissues alters how the music and musicians of the past are understood in the present. This article develops a theory of rock music reissues, analyzing them as cultural artifacts that transform the originals' historical meaning and cultural status. The influential role of paratextual and extratextual materials is closely analyzed through case studies of reissues of the Beach Boys' Pet Sounds, Gary Wilson's You Think You Really Know Me, and the various artists compilation Where the Action Is! L.A. Nuggets 1965–1968 . It is argued that the reissue process necessarily decodes a text's past and recodes it for the present, fundamentally altering our understanding of our cultural history.